Value and Efficacy of Foley Catheter Removal of Blunt Pediatric Esophageal Foreign Bodies. (30th January 2014) - Abdurehim, Yasin; Yasin, Yalkun; Yaming, Qu; Hua, Zhang
Abstract : Objective . To discuss the safety and efficacy of Foley catheter removal of blunt pediatric esophageal foreign bodies. Methods . Analyzing our first 17 cases of pediatric esophageal foreign bodies removed by Foley catheter method in respect of the efficacy, removal methods, and complications. We also reviewed related literature and discussed the background, current status, and technical matters that need attention of this method. Results . In three-year period between May 2010 and May 2013, in 16 out of 17 children blunt radiopaque foreign bodies impacted in the esophagus were successfully removed by a Foley catheter. There were no complications. In one patient, the foreign body was advanced into stomach and came out with stool 2 days later. Conclusions . The technique is safe, rapid, and cost-effective procedure and applicable for blunt, flat foreign bodies impacted in the esophagus.